Effet de la contamination de la litiere par les elements traces metalliques sur la survie et la croissance d’Armadillidium vulgare (Crustace, Isopode). - KHEMASSIA, Hajer; LOUATI, N.; NASRI-AMMAR , K. (INSTM Bulletin : Marine and Freshwater Sciences, 2019)
In order to highlight the physiological responses of Armadillidium vulgare to litter contamination by cadmium (Cd) and zinc (Zn), two experimental conditions are performed: single individual or groups of 10 individuals. The obtained results showed a weak mortality of individuals kept in groups confirming thus the resistance of this species to the applied trace elements. We also noticed that individuals tend to consume litter contaminated with Zn as well as the mixture Zn/Cd and avoid the litter contaminated by Cd. This avoidance behavior results in a loss of mass during the two firsts weeks of exposure to the lowest concentration.